Integrating data science and earth science : challenges and solutions - Bouwer, Laurens M. (SpringerBriefs in Earth System Sciences, 2022)
This open access book presents the results of three years collaboration between earth scientists and data scientist, in developing and applying data science methods for scientific discovery. The book will be highly beneficial for other researchers at senior and graduate level, interested in applying visual data exploration, computational approaches and scientifc workflows.